STUDI KASUS ASUHAN KEPERAWATAN GERONTIK PADA KELUARGA NY”M” DENGAN HIPERTENSI DIKELURAHAN BAROMBONG KECAMATAN TAMALATE KOTA MAKASSAR - Maria Sumaryati (Jurnal Ilmiah Kesehatan Sandi Husada, 2018)
Background: Health development is an effort to fulfill one of the basic rights of the community, namely the right to obtain health services in accordance with Article 29 H paragraph 1 of the 1945 Constitution and Law Number 23 of 1992 concerning health. This study aims to find out a general description of the Case Study of Mrs. M. with hypertension in the Barombong Sub-District, Tamalate Sub-District, Makassar City. The research method used is the case study method is a study that explores a nursing problem in detail, has in-depth data collection and includes various sources of information. The results of the research after being reviewed by Mrs. M in getting that lack of knowledge about Hypertension and the lack of information about one of the diseases that always occur in the elderly. After the Gerontik Nursing Care Act is done by the family, M. can understand the importance of how to overcome Hypertension problems by using herbal medicines or visiting the available community service centers, Health Education is an important factor in the implementation of Bringing Nursing Care for the Family.